2014
DOI: 10.1074/jbc.m113.479386
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Suppresses Expression of the Selenoprotein P Gene via an AMP-activated Kinase (AMPK)/FoxO3a Pathway in H4IIEC3 Hepatocytes

Abstract: Background:The suppression of selenoprotein P production may be a novel therapeutic target for reducing insulin resistance. Results: Selenoprotein P expression was suppressed by metformin treatment, but co-administration of AMPK inhibitor or FoxO3a siRNA cancelled this suppression. Conclusion: Metformin suppresses selenoprotein P expression via the AMPK/FoxO3a pathway. Significance: The AMPK/FoxO3a pathway in the liver may be a therapeutic target for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 43 publications
3
63
2
Order By: Relevance
“…However, reserpine inhibited the FHRE-Luc, and metformin, a well known AMPK activator, also inhibited FHRE-Luc activity. 18 These results suggest that there exist another signaling link between AMPK and FOXO3a dependent transcription.…”
Section: 6mentioning
confidence: 74%
“…However, reserpine inhibited the FHRE-Luc, and metformin, a well known AMPK activator, also inhibited FHRE-Luc activity. 18 These results suggest that there exist another signaling link between AMPK and FOXO3a dependent transcription.…”
Section: 6mentioning
confidence: 74%
“…Metformin, a biguanide that is used primarily to treat type 2 diabetes, has been reported to activate FOXO3 or its activator, AMPK, in various cell lines and in hepatocytes. 28,[30][31][32][33][34]67 We first determined the effect of metformin on FOXO3 expression and activity in human erythroid progenitor cells and found that metformin (1) We then treated human HSPCs with metformin to test our hypothesis that HbF could be induced. Our rationale was that, because knockdown of FOXO3 results in a decline in HbF, an increase in FOXO3 via drug induction would result in an increase in HbF (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Metformin, a biguanide class agent commonly used as an oral antidiabetic drug, has been shown to activate FOXO3 in nonerythroid cell lines and hepatocytes. 28,[30][31][32][33][34] Here, we investigate the role of FOXO3 in g-globin gene regulation through lentiviral expression, RNA interference, and induction by metformin.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of SeP in NAFLD remains to be well elucidated, even if they are able to act, as mentioned earlier, by their ability to modulate inflammatory response and insulin resistance. In addition, different evidence suggests that metformin improves systemic insulin sensitivity through the regulation of SeP production, suggesting a novel potential therapeutic approach to treating type 2 diabetes [185]. …”
Section: Liver-released Compoundsmentioning
confidence: 99%